Cerebral Oximetry for the Prediction of Neurological Dysfunction in Cardiosurgical Patients - A. N. Shepelyuk; T. V Klypa; Yu. V. Nikiforov (Общая реаниматология, 2011)
Objective: to study the efficiency of intraoperative transeosophageal echocardiography in the detection of indications for and contraindications to early activation in the operating room after myocardial revascularization under extracorporeal circulation. Subject and methods. One hundred and eighty-six patients aged 55.0±0.6 years were examined. A Sonos Agilent 5500 apparatus and a multipurpose Omni-2 transducer were used for ultrasound study. Left ventricular ejection fraction was determined in the four-chamber (Simpson) and transgastric views (visualization of the left ventricle in cross-section at the level of the papillary muscles). To identify impaired myocardial contractility hindering immediate activation, the authors analyzed the data of examining 142 patients who might undergo tracheal extubation in the operating room. A decreased left ventricular ejection fraction of less than 50% in the transgastric view was considered to be a contraindication to activation. The sensitivity of echocardiography in the differential diagnosis of acute myocardial infarction _ was studied in 44 patients with echocardiographic signs of acute myocardial ischemic lesion. Results. A left ventricular ejection fraction of less than 50% (41.5±2.2%) in the transgastric view was a refusal criterion for immediate patient activation. This group of patients, as compared with those having a left ventricular ejection fraction of 60.1±1.7%, had a longer duration of inotropic therapy (45.2±2.1 and 13±1.1 hrs; p<0.05) and a more prolonged length of postoperative intensive care unit stay (36.2±1.7 and 18.8±0.75 hrs; p<0.05). The correlation coefficient between the left ventricular ejection fraction at the end of surgery and the duration of inotropic therapy was 0.51 (p<0.0001) and that with an intensive care unit stay was 0.48 (p=0.00018). Among the patients with electrocardiographic signs of acute myocardial ischemic lesion, ultrasound study did not confirm the diagnosis in 65.9% of cases, which allowed early activation to be performed without complications. Acute akinesis of the left ventricular walls in 93.8% was a sign of acute myocardial infarction verified later on by X-ray contrast and laboratory studies. Conclusion. Transeosophageal echocardiographic monitoring is a highly effective diagnostic technique that can detect patients with left ventricular systolic dysfunction and verify acute ischemia and infarction of the myocardium, which substantially increases the safety of patient activation in the operating room after myocardial revascularization. Key words: ultrasound monitoring, transeosophageal echocardiography, early tracheal extubation, early activation of cardiosurgical patients, myocardial revascularization, aortocoronary bypass surgery.